2012
DOI: 10.1186/1471-2474-13-118
|View full text |Cite
|
Sign up to set email alerts
|

Effects of home-based resistance training and neuromuscular electrical stimulation in knee osteoarthritis: a randomized controlled trial

Abstract: BackgroundQuadriceps femoris muscle (QFM) weakness is a feature of knee osteoarthritis (OA) and exercise programs that strengthen this muscle group can improve function, disability and pain. Traditional supervised resistance exercise is however resource intensive and dependent on good adherence which can be challenging to achieve in patients with significant knee OA. Because of the limitations of traditional exercise programs, interest has been shown in the use of neuromuscular electrical stimulation (NMES) to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
114
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(124 citation statements)
references
References 27 publications
6
114
0
4
Order By: Relevance
“…In addition, the results of this study partly corroborate those of Bruce-Brand et al, 20 which identified improved functional ability and reduced pain after eight weeks of training with artificial electrical stimulation. However, these authors found no significant increase in isometric torque after eight weeks of training, a finding which differs from the results of the present study, in which there was a significant increase in isometric torque at the training angle after NMES training.…”
Section: Rosemffet Et Alsupporting
confidence: 81%
See 1 more Smart Citation
“…In addition, the results of this study partly corroborate those of Bruce-Brand et al, 20 which identified improved functional ability and reduced pain after eight weeks of training with artificial electrical stimulation. However, these authors found no significant increase in isometric torque after eight weeks of training, a finding which differs from the results of the present study, in which there was a significant increase in isometric torque at the training angle after NMES training.…”
Section: Rosemffet Et Alsupporting
confidence: 81%
“…However, these authors found no significant increase in isometric torque after eight weeks of training, a finding which differs from the results of the present study, in which there was a significant increase in isometric torque at the training angle after NMES training. These results may be related to the lower training time per-session and maintenance of the same training parameters for every session, without changing volume and intensity, used by Bruce-Brand et al, 20 compared to the present study. 16,21,22 In contrast, the present study conducted NMES training with only one knee flexion angle (90°), which resulted in increased torque after the training period solely for this angle, representing a possible limitation of the study.…”
Section: Rosemffet Et Almentioning
confidence: 48%
“…Scientific evidences used in this review show that the neuromuscular electrical stimulation (NMES) may be beneficial in patients with knee OA in variables such as pain (6,(23)(24)(25)(26), physical function (6,23,25), functional performance (25,27), discomfort (6), daily living activities (6) and stiffness (23,25). Furthermore, NMES seems to compensate physiological declines occurring in the muscle of patients, acting both in structure as in function of the quadriceps (23) by means of cross-sectional area increases (23,27) and muscular strength (23,25) and also in the improvement of voluntary muscle activation when combined with an exercise program (24).…”
Section: Neuromuscular Electrical Stimulationmentioning
confidence: 99%
“…Furthermore, NMES seems to compensate physiological declines occurring in the muscle of patients, acting both in structure as in function of the quadriceps (23) by means of cross-sectional area increases (23,27) and muscular strength (23,25) and also in the improvement of voluntary muscle activation when combined with an exercise program (24). The parameters used in these studies (6,(23)(24)(25)(26)(27) varied from: 50-80Hz, 100-400μs, intensity: visible muscle contraction until the maximum tolerated, time on: 10 seconds, off time: 10-50 seconds 15-45 minutes per session, for 12-36 sessions.…”
Section: Neuromuscular Electrical Stimulationmentioning
confidence: 99%
“…Table 1 summarizes the findings from randomized controlled trials on exercise and allied therapies in OA conducted in the last 5 years. [14][15][16][17]26,[33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] …”
Section: Review Of Literaturementioning
confidence: 99%